Glyphosate induces epithelial mesenchymal transition-related changes in human endometrial Ishikawa cells via estrogen receptor pathway. (15th June 2020) - Gastiazoro, M.P.; Durando, M.; Milesi, M.M.; Lorenz, V.; Vollmer, G.; Varayoud, J.; Zierau, O.
Abstract: Glyphosate based herbicides are the most commonly used herbicide in the world. We aimed to determine whether glyphosate (Gly) induces epithelial mesenchymal transition (EMT) - related changes in a human endometrial carcinoma cell line (Ishikawa cells), and whether the estrogen receptor (ER) pathway is involved in these changes. Ishikawa cells were exposed to Gly (0.2 μM and 2 μM) or 17β-estradiol (E2: 10 −9 M). We detected that Gly increased cell migration and invasion ability compared to vehicle, as did E2. Moreover, a down regulation of E-cadherin mRNA expression was determined in response to Gly, similar to E2-effects. These results show that Gly promotes EMT-related changes in Ishikawa cells. When an ER antagonist (Fulvestrant: 10 −7 M) was co-administrated with Gly, all changes were reversed, suggesting that Gly might promote EMT-related changes via ER-dependent pathway. Our results are interesting evidences of Gly effects on endometrial cancer progression via the ER-dependent pathway. Highlights: Glyphosate produced an increase on migration and invasion ability in Ishikawa endometrial cancer cells, as did estradiol. E-Cadherin mRNA expression was down-regulated in Ishikawa endometrial cancer cells after glyphosate and estradiol treatments. Fulvestrant plus glyphosate or estradiol reverts the induced changes by glyphosate and estradiol alone treatments.